Panorama da indústria de baterias automotivas: tecnologias da transição para eletrificação - Ferreira, Adrianus de Queiroz (2019)
Due to the global trend towards more sustainable energy matrices, the automobile industry is going through the process of converting the internal combustion engine, powered by fossil fuels, to the electric motor, powered by lithium ion batteries. Through the review of several scientific texts and market analysis, this paper seeks to give an overview of this process and the technologies involved in this transition, as well as to analyze Brazil's position in this worldwide transformation. With an industrial park devoted exclusively to lead acid battery production and, due to the consolidated agricultural sector, with most recent research investments focused on biofuels production, Brazil faces difficulties to keep up with automobile electrification.